2018
DOI: 10.1172/jci.insight.120196
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin-2 derived from adipose tissue mediates aldosterone-induced renal injury

Abstract: Lipocalin-2 is not only a sensitive biomarker, but it also contributes to the pathogenesis of renal injuries. The present study demonstrates that adipose tissue-derived lipocalin-2 plays a critical role in causing both chronic and acute renal injuries. Four-week treatment with aldosterone and high salt after uninephrectomy (ANS) significantly increased both circulating and urinary lipocalin-2, and it induced glomerular and tubular injuries in kidneys of WT mice. Despite increased renal expression of lcn2 and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 89 publications
3
26
0
Order By: Relevance
“…They also demonstrate that incubating recombinant LCN2 with adipose tissues (≥16hr incubation) from LCN2KO mice resulted in removal of polyamination [65]. Further, the same group demonstrated that adipose-derived LCN2 can also mediate both acute and chronic renal injuries and that this is independent of kidney-derived LCN2 [67]. In contrast, cell-type-resolved liver proteomics revealed that LCN2 is predominantly secreted by Kupffer cells (hepatic macrophages) and not the hepatocytes, implying that increased LCN2 expression in the liver signifies an inflammatory environment in response to obesity [68].…”
Section: Resultsmentioning
confidence: 99%
“…They also demonstrate that incubating recombinant LCN2 with adipose tissues (≥16hr incubation) from LCN2KO mice resulted in removal of polyamination [65]. Further, the same group demonstrated that adipose-derived LCN2 can also mediate both acute and chronic renal injuries and that this is independent of kidney-derived LCN2 [67]. In contrast, cell-type-resolved liver proteomics revealed that LCN2 is predominantly secreted by Kupffer cells (hepatic macrophages) and not the hepatocytes, implying that increased LCN2 expression in the liver signifies an inflammatory environment in response to obesity [68].…”
Section: Resultsmentioning
confidence: 99%
“…It is produced by adipocytes at high levels in mice and humans in response to inflammatory stimuli and the impact of age on this proinflammatory adipokine is unknown ( 95 , 96 ). However, adipose tissue-derived LCN2 has been shown to promote the pathogenesis of renal injury, a condition that is more prevalent in aged individuals with type 2 diabetes ( 97 , 98 ). In addition, it may also play an important proinflammatory role in adipose tissue remodeling during visceral fat expansion ( 99 ).…”
Section: Effects Of Aging On Adipose Tissue Adipokine Secretionmentioning
confidence: 99%
“…As such, increased circulating LCN2 is often used as a pathological biomarker such as acute kidney injury [ 102 ]. In pathological conditions, it was shown that two other forms of LCN2—R81E and deamidated LCN2—were expressed at least in WAT [ 95 , 103 ]. Thus, pathological forms of LCN2 probably display diverse ligand-binding and post-translation modifications, depending on the different tissue/cell sources, further complicating their causal roles in acute and chronic diseases.…”
Section: Chronic Inflammation During the Development Of Type 2 Diabetmentioning
confidence: 99%